5-28а
Объяснение:
=(7а)²-2*7а*2+2²-((7а)²-1²)=(7а)²-28а+4-(7а)²+1=5-28а
1) (7а - 2)² = 49а² - 2*7а*2 + 4 = 49а² - 28а + 4
2) (7а - 1)(7а + 1) =
49а² + 7а - 7а - 1 = 49а² - 1
3) (49а² - 28а + 4) - (49а² - 1) =
49а² - 28а + 4 - 49а² + 1 = -28а + 5
5-28а
Объяснение:
=(7а)²-2*7а*2+2²-((7а)²-1²)=(7а)²-28а+4-(7а)²+1=5-28а
Объяснение:
1) (7а - 2)² = 49а² - 2*7а*2 + 4 = 49а² - 28а + 4
2) (7а - 1)(7а + 1) =
49а² + 7а - 7а - 1 = 49а² - 1
3) (49а² - 28а + 4) - (49а² - 1) =
49а² - 28а + 4 - 49а² + 1 = -28а + 5